ORGANIZING A VALUE-BASED BUDGETING SYSTEM IN IMPROVING MANAGEMENT DECISIONS IN JOINT STOCK COMPANIES (Marketing Journal, 2025)
This article analyzes the foundations of the organization of a value -based budgeting system to improve management decisions in joint -stock companies. The study covers the concept of Value -Based Management (VBM) and the mechanisms for its practical applicat ion. The budgeting system, as a corporate management tool, is evaluated as a mechanism that combines strategic planning, control and analysis processes into a single cycle. The article analyzes the practical effectiveness of value -based budgeting based on the combination of economic value added (EVA) and balanced scorecard (BSC) models. Using the example of “Regional Electric Networks ” JSC, an assessment was conducted based on economic indicators for 2020 -2024, and the dynamics of value creation and its impact on management decisions were determined. According to the results of the study, the value -based budgeting system is recommended as an important tool for increasing share holder value, effective use of capital, and ensuring strategic stability.
Keywords: joint-stock company; value -based management; budgeting; economic value added (EVA); balanced scorecard (BSC); return on capital; management decisions; strategic sustainability